Electronic Commerce and Customer Relationship Management: Integration of Technologies into Marketing Strategy - Al-Ababneh, Hassan Ali; Al Muala, Ayed Moh’d (International Review of Management and Marketing, 2025)
In the context of rapidly evolving digital markets, e-commerce is no longer limited to transactional functions but is increasingly perceived as a strategic framework for managing long-term customer relationships. Intensifying competition, the diversification of consumer preferences, and the acceleration of technological innovation necessitate a revision of conventional customer relationship management (CRM) approaches. This study aims to explore how the integration of digital technologies into e-commerce marketing strategies influences the development of personalized, sustainable, and value- driven interactions with customers. The relevance of the research lies in the growing demand for adaptive marketing models capable of enhancing customer engagement, trust, and retention in highly dynamic digital environments. The research employs a mixed methodology, combining literature review, comparative case analysis of global e-commerce firms, and interpretation of customer performance indicators through factor-based assessment. The findings reveal a significant correlation between the level of CRM digitalization and improvements in customer lifetime value, satisfaction, and behavioral loyalty. Practical implications include recommendations for integrating data analytics, automation tools, and AI-driven personalization mechanisms into existing marketing infrastructures. The results are particularly relevant for companies aiming to strengthen customer-centric strategies and optimize user experience in competitive digital ecosystems.